Consentement à payer pour le riz local de qualité au Burkina Faso : une analyse par la méthode des enchères expérimentales - Ouédraogo, Mathieu (African Association of Agricultural Economists, 2021)
This study analyses the willingness to buy and to pay for local rice in Burkina Faso. Women consumers’ preferences and their willingness to pay for local Bagré rice were revealed through experimental auctions conducted among 120 women from Ouagadougou city. The study shows that 55% of the participants in the experimental auctions preferred local rice to the imported one. About 74% of consumers were willing to pay an average additional premium of 100 CFA/kg compared to the price of imported rice (Thai 5% broken) to acquire parboiled Bagré rice. Seventy-five percent were willing to pay an average surcharge of 87 CFA per kg for the non-parboiled quality Bagré rice. The study concludes that there is a potential urban demand for local quality rice. Processors should invest in rice quality by ensuring that the additional investment costs are lower than the premiums expressed by consumers.